Learning Development and Instilling PAI Values as the Formation of the Religious Character of Islamic Elementary School Students - Hanik Afidatur Rofiah; Muhammad Munadi (al-Afkar, Journal For Islamic Studies, 2024)
This article discusses the important role of Islamic religious education in developing religious character in elementary school students. The discussion covers two main aspects, namely developing learning patterns and instilling PAI values. The instillation of Islamic religious values ​​has a crucial role in shaping the character of students who are devout, honest, tolerant and empathetic. Values ​​such as compassion, mutual assistance and respect for fellow humans are at the core of developing religious character. This article also reveals the importance of developing PAI learning patterns which aim to revive something that was once alive and an important part but then experienced setbacks or degradation. In Islamic religious education, new strategies for religious-based character education need to be re-emerged so that it becomes a vital part and can again receive the main focus by all parties. The methodology of this research is qualitative descriptive, this research uses a single case study. Data sources include objects, places, events, informants and documents. Data collection techniques in this research are observation, interviews and document analysis. Instilling Islamic Religious Values ​​as a Foundation for Religious Character Islamic Religious Education introduces students to basic concepts in religion such as monotheism, worship, morals and Islamic history. Students learn about the oneness of God, the obligation of worship, and moral values ​​in Islam. It is important for students to understand and appreciate these teachings as the basis for a strong religious character. The process of Islamic religious education in schools has carried out new developments towards character formation so that later it can be reflected in students' life behavior. This development is an effort to revive something that was once alive and an important part but then experienced setbacks or degradation.